A prospective assessment of aortic root changes in individuals with undifferentiated congenital connective tissue dysplasia using a modified method for determining the reference diameter of the aortic root - A. A. Semenkin; E. V. Semenova; O. I. Chindareva; E. N. Loginova; G. I. Nechaeva (Лечащий Врач)
The article presents results of a prospective assessment of changes in aortic root in individuals with undifferentiated congenital connective tissue dysplasia using a modified method for determining the reference diameter of the aortic root and the possibility of medical treatment of aortic root enlargement in the presence of connective tissue dysplasia.